Correlation between the Plasma Magnesium Levels and Glycated Haemoglobin in Sudanese Patients with Type 2 Diabetes Mellitus in Khartoum State: A Cross Sectional Study - Seedahmed, Tilal Abd El-Hameed; Ahmed, Samia Mahdi (Current Approaches in Science and Technology Research Vol. 12, 2021)
This is a cross-sectional study with the goal of evaluating the plasma levels of magnesium and HbA1C in (60) patients with type 2 diabetes mellitus and (40) apparently healthy (non-diabetic) volunteers as a control group. The patients were recruited from various hospitals and centres. The test and control groups were matched in terms of age and gender. A spectrophotometer was used to assess magnesium levels in the blood (Bio system Company reagents).The levels of HbA1C were determined using reagents and instruments from NycoCard company. SPSS was used to examine the data.The results revealed a considerable decreasein the mean of the plasma levels of magnesium of the diabetic group when compared with the control group (p. value <0.05), whereas HbA1C were increased in diabetic patients (type 2) compared to the control group (p. value <0.05). However, among diabetic patients, there was a strong negative correlation between magnesium plasma levels and HbA1C levels, as well as a weak negative correlation between magnesium plasma levels and duration of disease.Plasma levels of magnesium have a strong negative correlation with HbA1C levels, the findings demonstrated thatuncontrolled diabetic patients are at higher risk of hypomagnesaemia compared to controlled patients.